Photosensitization in Cattle Caused by Spontaneous and Experimentally Ingestion of Stryphnodendron fissuratum - Lazaro, Neylisa Dario; Bacha, Flavia Barbieri; Pupin, Rayane Chitolina; Paula, Juliana Paniago Lordello de; Leal, Paula Velozo; Pott, Arnildo; Gomes, Danilo Carloto; Lemos, Ricardo Antônio Amaral de (Acta Scientiae Veterinariae, 2018)
Background: Stryphnodendron fissuratum is a tree from the Brazilian Cerrado. Its fruit is toxic to cattle and can cause clinical digestive signs, hepatogenous photosensitization, and abortion. Cases of poisoning in cattle, goats and guinea pigs have been experimentally reproduced; however, photosensitization could not be reproduced. The aim of this work was to describe an outbreak of natural poisoning and experimental reproduction in cattle, both with hepatogenous photosensitization. Materials, Methods & Results: Its described and natural outbreak and an experimental poisoning. In the outbreak, three bovines in the acute phase and three in the chronic phase were examined. Blood samples were collected from all of these animals in order to measure serum levels of aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), urea, and creatinine. The first three animals underwent necropsy and histopathological evaluation. The experiment was conducted with two nine-month-old calves that received an oral paste made with crushed S. fissuratum fruits mixed with water. These fruits were collected at a farm at which cattle poisoning cases had occurred. Blood samples were collected in order to measure serum levels of AST, GGT, urea, and creatinine, before plant administration and then daily during the experimental period. Skin biopsies were taken before plant administration and new one after the first signs of skin lesions. The natural outbreak affected 52 of 160 bovine (31 calves and 21 cows) in the lot. Two calves and 14 cows died. Clinical signs consisted of depression, ataxia, incoordination, behavioral changes, decubitus, and death. One animal that died and 36 others that recovered had photodermatitis. Necropsy findings in the animals consisted of bad corporal condition, pale kidneys, evidence of liver lobular pattern, dry rumen contents, and full bladder. In two animals, fruit seeds were found in the rumen, and one animal had ulcers and transmural edema in the abomasum. Microscopically, mild to moderate renal tubular distension, accumulation of proteinaceous material in lumen with mild to moderate swelling, and epithelial necrosis. In the liver, swelling of hepatocytes and moderate bile stasis was detected. Enzymes values in all evaluated bovines were higher than those considered normal for the species. Experimentally, both calves became ill and one died. The clinical signs were apathy, inappetence, wobbling, weight loss, and goosebumps. One of them had jaundice, tearing, photophobia, ear skin detachment, and ulcers at the muzzle, nostrils and ventral face of the tongue. This animal was euthanized in extremis, and the necropsy findings showed generalized jaundice, evidence of increased liver lobular pattern, thick bile, pale kidneys, and esophageal, tongue, and epiglottal ulcers. Microscopically, the lesions were similar to those described during the natural outbreak. The skin biopsy from the calf that recovered showed perivascular edema and mild eosinophilia. Discussion: The diagnosis was made based on clinical signs, necropsy findings, histopathological lesions, and epidemiological analysis. Experimentally, the plant was toxic at the administered doses. Photosensitization was the most common clinical sign during the natural outbreak and until now, has never been experimentally reproduced. Based on histopathological lesions observed in this study, we can consider that is from hepatogenous origin. The results showed that the kidney lesions have an important role during the pathogenesis caused by this poisoning and during disease evolution.